Liberal Hermeneutics of the Spectacular in the Study of the New Testament and the Roman Empire - Zeichmann, Christopher B. (Method & theory in the study of religion, 2019)
Since 9/11, there has been a surge in interest in the topic of violence both among scholars of religion and in the humanities more broadly. This article suggests that such works operate with a "hermeneutics of the spectacular" that functions to legitimate the liberal status quo by concentrating its focus upon the most visibly heinous forms of state violence under the aegis of a politics of "resistance." This article uses the New Testament and its depiction of the military as a site for thinking about how folk definitions come to classify certain activities as "violent" and not others, both today and in antiquity. If biblical scholarship—or the study of religion more broadly—is to be something other than an ideological repository for late capitalism, it is necessary to reconsider the issue. This article, by point of contrast, discusses three theoretical approaches to violence that may be useful: Objective-Structural Violence, Symbolic Violence, and Violent Subjectivities.